ICT Usage and MSEs Growth: Evidence from Indonesia - Sutaryo Sutaryo; Muhtar Muhtar; Jaka Winarna; Prihatnolo Gandhi Amidjaya (Journal Of Business, Finance, and Economics (JBFE), 2025)
This study aims to examine the influence of the level of ICT usage in a region on the MSEs growth in Indonesia using a quantitative approach. This study uses secondary provincial-level data obtained from the Statistics Indonesia (BPS) and the Financial Services Authority (OJK), which are analyzed using descriptive statistics, correlation, and panel data regression. The study findings indicate that the level of ICT usage in a region has a positive effect on the MSEs growth in Indonesia. However, there are differences in the impact between regions, where the positive effect of ICT usage on MSE growth is consistent in the west Indonesia region, but not significant in the east Indonesia region. The researcher recommends that the government and other stakeholders pay more attention to the development of ICT infrastructure in Indonesia, particularly improving ICT in eastern Indonesia to create equality in technology utilization. In addition, increasing digital literacy and training for MSEs in Indonesia is crucial so they can utilize technology optimally. Thus, it is hoped that the positive effect of ICT usage on MSEs can be felt evenly throughout Indonesia.